2022
DOI: 10.3390/ijerph19148862
|View full text |Cite
|
Sign up to set email alerts
|

Association between Leptin (G2548A) and Leptin Receptor (Q223R) Polymorphisms with Plasma Leptin, BMI, Stress, Sleep and Eating Patterns among the Multiethnic Young Malaysian Adult Population from a Healthcare University

Abstract: Relative leptin resistance in childhood to absolute leptin resistance in maturity suggests sleep, eating behaviour, and the psychological state as probable causes. The current body of research provides inconclusive evidence linking G2548A and Q223R to obesity. Furthermore, we could find very little data that have observed the association between the environment and gene polymorphism, especially in the multiethnic population that exists in Malaysia. This study searched for a possible link between sleeping habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 104 publications
2
0
0
Order By: Relevance
“…The weight loss and endocrine changes after surgery are in accordance with other reports (Sjostrom, 2013;Herder et al, 2014). The positive association between leptin and BMI and negative association between leptin and male sex are known from other studies (Rosenbaum and Leibel, 2014;Mohanraj et al, 2022). The sex-related differences in the associations between leptin and the POPs might be due to the sex-related differences in the associations between leptin and BMI.…”
Section: Discussionsupporting
confidence: 90%
“…The weight loss and endocrine changes after surgery are in accordance with other reports (Sjostrom, 2013;Herder et al, 2014). The positive association between leptin and BMI and negative association between leptin and male sex are known from other studies (Rosenbaum and Leibel, 2014;Mohanraj et al, 2022). The sex-related differences in the associations between leptin and the POPs might be due to the sex-related differences in the associations between leptin and BMI.…”
Section: Discussionsupporting
confidence: 90%
“…However, contrary to many previous studies, we did not find any association between the concentration of circulating leptin and the BMI of patients 21 , 44 46 . Although, as in our study, several reports also found no correlation between BMI and leptin levels 47 . Higher serum leptin levels have been shown to correlate with lower BMI in childhood and a reduced predisposition to developing metabolic disorders in adolescence and adulthood 48 .…”
Section: Discussionsupporting
confidence: 52%